Clinical study of neonatal septicemia with reference to early indicators of sepsis - Kishore, E.; S. V. S., Sreedhar (International Journal of Contemporary Pediatrics, 2017)
Background: The use of CRP (C-reactive protein) in early diagnosis of neonatal septicemia. The usefulness of CRP in early detection of neonatal septicemia/meningitis and urinary tract infection was studied in a neonatal unit using a semi-quantitative latex-agglutination as a rapid screening method and electroimmuno assay as reference method for CRP determination. Methods: The present study was conducted among 150 patients 218 samples were taken for serum globulin determinations. Additionally, all infants born at the hospital throughout August 2016 to February 2017 with a designation of blood disease, infectious disease or tract infection (UTI) were retrospectively studied. Depending on the clinical course and therefore the results of the culture the 110 infants were divided into four groups. Results: The 110 infants in 92% of non-infected infants CRP was 16 mg/l and 80% had CRP <10 mg/l up to 3 days of age. After 3 days of age 93% had CRP <12 mg/l. The initial CRP level was increased in 9 out of 11 patients (82%) with bacterial septicemia. Low CRP was seen in one patient with total agranulocytosis and septicemia from Streptococcus type B and in one patient with Staphylococcus albus sepsis. A rise in CRP was also seen in very pre-term infants with septicemia. Increased initial CRP was uncommon in neonatal urinary tract infection (2 of 9) but a rise was seen in 3 additional patients. Conclusions: A comparison between CRP, total neutrophil blood cell count and hand neutrophil count as diagnostic parameters was in favor of CRP at this early stage of infection. CRP is of definite value as an aid in early diagnosis of neonatal septicemia and bacterial meningitis.